Manajemen pemberdayaan diabetes berdasarkan promosi kesehatan kepada keluarga pasien diabetes. - Ambarika, Rahmania; Wardhani, Lingga Kusuma; Aulia, Hana Agustin; Putra, Made Mahaguna (State Islamic University of Sunan Ampel, 2025)
The 2023 Indonesia Health Survey results showed an increase compared to the prevalence of diabetes mellitus in the population aged ≥15 years—indicating the need for effective interventions to carry out self-care management in diabetic patients. Therefore, this study aimed to determine the effect of family empowerment-based health promotion interventions on glycemic control, diabetes patient self-care, diabetes self-management, self-motivation, and perception of disease in patients with type 2 diabetes. This study examined the effect of family empowerment-based health promotion interventions to improve glycemic control, diabetes patient self-care, diabetes self-management, self-motivation, and perception of disease in patients with type 2 diabetes. Empowerment-based health promotion interventions for families affected self-motivation (p=0.00), family support (p=0.00), and self-care in diabetic patients (p=0.00). The study results showed that patient empowerment-based training, carried out with cooperation and centralisation of patients and their families, played an essential role in obtaining correct health behaviours and achieving independence for patients with diabetes and other chronic diseases in taking care of themselves.